Thiocyanate- and thiol-functionalized p-doped quantum dot colloids for the development of bulk homojunction solar cells - Dambhare, V. Neha; Sharma, Ashish; Mahajan, Chandan; Rath, Arup K. (Energy Technology, 2022)
Progress in device engineering and surface passivation strategies has led to steady progress in colloidal quantum dot (QD) solar cells. Bulk homojunction (BHJ) device architecture has several advantages over the conventional planar junction in developing QD solar cells. Herein, surface ligand chemistry is utilized to control the doping type and dispersibility of oppositely doped PbS QDs to develop BHJ solar cells. Thiocyanate and thiol ligand combination is introduced to develop p-PbS QD ink, which is blended with halide-passivated n-PbS QDs to build BHJ solar cells. It is shown that BHJ solar cells are benefited from high energy offset and higher hole mobility. This leads to the superior carrier extraction from a thicker active layer without compromising fill factor and open circuit voltage. Power conversion efficiency has reached 10.7% in 530 nm-thick BHJ solar cells, a 24% improvement over the best performing planar solar cells. With the help of the 1D solar cell capacitance simulator, it is shown that a 15% efficient QD solar cell can be realized by further improving the hole mobility above 0.1 cm(2) V-1 s(-1).
Keywords: bulk homojunctions; Doping; quantum dots; solar cells; surface functionalization